Hutan Rakyat dan Serbuan Pasar: Studi Refleksi Pengusahaan Hutan Rakyat Lestari secara Kolaboratif di Pacitan, Jawa Timur - Bambang Siswoyo (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2007)
Market-oriented exploitation in managing lndonesian forest has led to the enaironmental problems. Such process has also created economic problems for local people who live around the forest as their economic resources are declining significantly. This paper argues that collaborative forest management involving non-governmental organization, local communities, priaate sector and government may enhance the economic welfare of local communities; while at the same time preserve ecological of the forest